Soviet catches of whales in the North Pacific: revised totals - Ivashenko, Y. V.; Clapham, P. J.; Brownell Jr., R. L. (J. Cetacean Res. Manage., 2023)
The USSR conducted a global campaign of illegal whaling beginning in 1948. Catch records for Soviet pelagic operations in the Southern Hemisphere (and the northern Indian Ocean) have been largely corrected, but major gaps have remained for the North Pacific. Here, using newly discovered whaling industry reports, corrected figures for Soviet catches in this ocean are provided. During the period 1948–79, a minimum of 190,183 whales were killed by the USSR in the North Pacific (195,783 if one includes an estimate for sperm whales taken in years for which there are no true data); of these, only 169,638 were reported to the IWC, a difference of 20,568 whales (26,168 including the sperm whale estimate). Figures were falsified for 8 of 12 hunted species, with some catches over-reported to camouflage takes of illegal species. Revised catch totals (caught vs. reported) are as follows: blue whale – 1,621 vs. 858; fin whale – 14,167 vs. 15,445; humpback whale – 7,334 vs. 4,680; sperm whale – 153,686 vs. 132,505; sei whale – 7,698 vs. 11,363; North Pacific right whale – 681 vs. 11; bowhead whale – 145 vs. 0; gray whale – 172 vs. 24. Bryde’s, minke, killer and Baird’s beaked whale catches were reported correctly. Of all the hunted species, sperm and North Pacific right whales were the most heavily impacted. Major falsifications for sperm whales involved figures for both total catch and sex ratio.